Antimicrobial studies of beta-caryophyllene and 1,8-cineol against gram-positive and gram-negative bacteria - Moo, Chew Li (2021)
The discovery and introduction of antibiotics to treat bacterial infections have almost successfully eradicated the threats posed by infectious bacteria. However, the misuse of antibiotics such as over-prescription of antibiotics and patient’s non-compliance in completing the antibiotic course have led to the development of resistance in microorganisms due to the natural selection process. Consequently, novel antibiotics or alternatives have to be developed and discovered in order to mitigate this resistance. In this study, two compounds, beta-caryophyllene (BCP) and 1,8-cineol (CN), were first screened against several bacteria such as Bacillus cereus, Escherichia coli as well as multidrugresistant strains Klebsiella pneumoniae to assess the antibacterial effects, followed by a few assays to evaluate the modes of action of the two mentioned compounds. We found that BCP and CN exhibited antibacterial effect against B. cereus and Klebsiella pneumoniae carbapenemase-producing K. pneumoniae (KPC-KP) with the minimum inhibitory concentration (MIC) of 2.50 % (v/v) and 3.13 % (v/v) respectively. Time-kill analysis was performed to evaluate the killing kinetics of the compounds. Results show that BCP and CN was bactericidal against B. cereus and KPC-KP based on the reduction number of ≥ 3 log10 in CFU/mL. Subsequently, zeta-potential measurement, measurement of UV-absorbing materials, ethidium bromide influx/efflux assay, outer membrane permeability assay, scanning and transmission electron microscopies, oxidative stress evaluation and lipid peroxidation were performed to evaluate the modes of action of the compounds. The results obtained from various assays showed increased in membrane permeability and leakage of UVabsorbing materials (protein and nucleic acid) in BCP and CN-treated cultures, showing that both BCP and CN played a role in disrupting the bacterial membrane. Ethidium bromide influx/efflux assay showed that the influx of compounds into the bacterial cells was due to damaged membrane caused by BCP and CN. In addition, measurement of reactive oxygen species (ROS) and lipid peroxidation in CN-treated KPC-KP cells revealed that CN caused increase in ROS and malondialdehyde levels. The morphology of KPC-KP cells treated with CN showed corrugated surfaces and irregular rod-shaped forms under scanning electron microscopic analysis, as well as cytoplasmic clear zones due to intracellular leakage and damaged membrane in transmission electron microscopic analysis. In conclusion, BCP causes increase in membrane permeability, intracellular leakage and membrane disruption. CN induced oxidative stress which leads to lipid oxidation, affecting the membrane permeability, intracellular leakage and eventually disruption in the bacterial membrane, resulting in cell death. This study investigated the mechanisms of action of BCP and CN in bacterial membrane disruptions. The findings of this study could be helpful in the future employment of BCP and CN as novel alternatives for existing antibacterial agents in the clinical setting.